On extending de Bruijn sequences - Becher, Veronica Andrea (2011)
We give a complete proof of the following theorem: Every de Bruijn sequence of order n in at least three symbols can be extended to a de Bruijn sequence of order n+1. Every de Bruijn sequence of order n in two symbols can not be extended to order n+1, but it can be extended to order n+2. © 2011 Elsevier B.V.